Fatores associados à insegurança alimentar em crianças atendidas em ambulatório de pediatria de um hospital universitário do Rio de Janeiro - Araujo, Thamiris Fernandes (2024)
Food Insecurity (FI) is a global public health issue, especially in economically vulnerable regions. Its severity is particularly highlighted in children, who are more susceptible to the impacts of FI, such as impaired physical and cognitive development. Studies show the association between FI and child health; however, more research is needed to understand the multiple factors involved. Objective: To evaluate the factors associated with FI in children attending a hospital in Rio de Janeiro. Methods: Cross-sectional study with children aged 6 months to 9 years and 11 months, of both sexes. The nutritional status was assessed based on anthropometric indices according to the World Health Organization (WHO) guidelines. The Brazilian Food Insecurity Scale (EBIA) was used to evaluate FI. Statistical analysis included simple and multivariate logistic regression, with a 95% confidence interval. Results: A total of 223 children were assessed, of whom 52% (n=116) were female, with a mean age of 4.9±2.9 years, and 20.6% (n=46) were under 24 months of age. Regarding nutritional status, 71.8% (n=160) were of normal weight (eutrophy) and 23.3% were overweight (overweight and obesity; n=52). The prevalence of mild FI was 51.1%, moderate FI was 16.6%, and severe FI was 7.2%. Children with moderate-to-severe FI consumed more processed meats (p=0.045) and sugary beverages (p=0.025). Among children aged 24 months and older, fewer meals were observed in those with higher levels of FI (p=0.045). Factors such as income (OR = 0.40; IC 0,2-0,7; p = 0.001) and age under 24 months (OR = 4.31; IC 1,3-17,9; p = 0.044) were significantly associated with the outcome. Conclusion: FI negatively impacts children's health, particularly among younger children and those from lower-income households. The study underscores the need for public policies addressing adequate nutrition and socioeconomic factors as crucial aspects to reduce FI and its effects on child development.